EVALUATION OF KAWASAKI DISEASE RISK SCORING SYSTEMS FOR INTRAVENOUS IMMUNOGLOBULIN RESISTANCE - Sleeper, Lynn A. (2010)
OBJECTIVES: To assess the performance of three risk scores from Japan that were developed to predict, in children with Kawasaki disease, resistance to intravenous immunoglobulin (IVIG) treatment. STUDY DESIGN: We used data from a randomized trial of pulsed steroids for primary treatment of Kawasaki disease to assess operating characteristics of the three risk scores, and we examined whether steroid therapy lowers the risk of coronary artery abnormalities in patients prospectively classified as IVIG resistant. RESULTS: For comparability with published cohorts, we analyzed the data of 99 patients not treated with steroids (16% IVIG-retreated), and identified male sex, lower albumin and higher AST as independent risk factors for IVIG resistance. The Kobayashi score was similar in IVIG-resistant and responsive patients, yielding sensitivity=33% and specificity=87%. There was no interaction of high vs. low risk status by treatment received (steroid vs. placebo) using any of the three risk score algorithms. CONCLUSION: Risk scoring systems from Japan have good specificity but low sensitivity for predicting IVIG resistance in a North American cohort. Primary steroid therapy did not improve coronary outcomes among patients prospectively classified as high risk for IVIG resistance.